2020
DOI: 10.18632/aging.102934
|View full text |Cite
|
Sign up to set email alerts
|

Intermedin1-53 attenuates aging-associated vascular calcification in rats by upregulating sirtuin 1

Abstract: Vascular calcification is a common phenomenon in older adults. Intermedin (IMD) is a cardiovascular bioactive peptide inhibiting vascular calcification. In this study, we aimed to investigate whether IMD1-53 attenuates aging-associated vascular calcification. Vascular calcification was induced by vitamin D3 plus nicotine (VDN) in young and old rats. The calcification in aortas was more severe in old rats treated with VDN than young control rats, and IMD expression was lower. Exogenous administration of IMD1-53… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 51 publications
1
30
0
Order By: Relevance
“…In line with these findings, metformin ameliorated VSMC calcification in vitro through AMPK activation [ 59 ]. Additionally, both the peptide ghrelin and the protein intermedin 1-53 (IM 1-53 ) attenuated VCN through AMPK activation both, in vivo and in vitro [ 60 , 61 ]. Ghrelin induced both LC3-II and Beclin1 while IM 1-53 upregulated Sirt1 expression.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In line with these findings, metformin ameliorated VSMC calcification in vitro through AMPK activation [ 59 ]. Additionally, both the peptide ghrelin and the protein intermedin 1-53 (IM 1-53 ) attenuated VCN through AMPK activation both, in vivo and in vitro [ 60 , 61 ]. Ghrelin induced both LC3-II and Beclin1 while IM 1-53 upregulated Sirt1 expression.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, intermedin 1-53 (IM 1-53 ) also ameliorated VCN while the authors additionally observed a marked increase in Klotho expression after IM 1-53 treatment. This increase in Klotho expression by IM 1-53 , is possibly the consequence of AMPK-dependent inhibition of mTOR [ 60 ]. Indeed, there are multiple lines of evidence supporting AMPK as an anti-VSMC calcification mechanism.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…unOC can upregulate the expression levels of p-PKA, p-AMPK and SIRT1. As PKA and AMPK regulate SIRT1 in cell differentiation (37,38), the PKA-AMPK pathway was examined to find if it was required for unOC to promote osteogenic differentiation in BMSCs. The PKA inhibitor, H89, was used to detect the signaling pathway through which unOC regulated the differentiation of mouse BMSCs.…”
Section: Unoc Promotes Osteogenic Differentiation Of Bmscs Through Pka-ampk-sirt1mentioning
confidence: 99%